Tissue factor pathway inhibitor deficiency enhances neointimal proliferation and formation in a murine model of vascular remodelling - Singh, Ripudamanjit; Pan, Shuchong; Mueske, Cheryl S.; Witt, Tyra A.; Kleppe, Laurel S.; Peterson, Timothy E.; Caplice, Noel M.; Simari, Robert D. (Thrombosis and Haemostasis, 2003)
Tissue factor (TF) is a small-molecular-weight glycoprotein that initiates the extrinsic coagulation pathway but may have important noncoagulation vascular functions as well. Tissue factor pathway inhibitor (TFPI) is a major physiological inhibitor of TF-initiated coagulation. Enhancement of vascular TFPI either by overexpression using gene transfer or delivery of protein to the vessel has been shown to reduce neointimal formation. However, the inherent role of TFPI in this process has not been defined. To do so, we utilized a murine model of vascular remodeling using flow cessation in mice, which are heterozygous for a genetic deletion of the first Kunitz domain of TFPI or wild type littermates. The heterozygotic mice had 50% of wild type TFPI activity in plasma as well as vascular homogenates. To study the effect of TFPI deficiency on neointimal formation, age matched TFPIK1+/- and wildtype littermates underwent unilateral common carotid artery ligation. Mice were sacrificed at 4 weeks and the ligated carotid arteries were analyzed. There was a significantly greater neointima to media ratio and less luminal area in the TFPIK1+/- mice compared to their TFPIK1+/+ littermates. The proliferative index of intimal cells in TFPIK1+/-mice at 1 week was significantly higher compared to TFPIK1+/+mice. We conclude that TFPI deficiency enhances neointimal formation and proliferation associated with flow cessation. This suggests that TFPI may regulate vascular remodeling primarily through modulation of neointimal formation.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Thrombosis; remodeling; neointima; tissue factor; inhibitors